TESTING OF WEAK FORM MARKET EFFICIENCY ON INDONESIAN CAPITAL MARKET : STUDY ON LQ45 COMPANIES ON THE INDONESIA STOCK EXCHANGE - wati, Nilma - (Journal of International Conference Proceedings, 2022)
The purpose of this research is to determine whether or not the Indonesian capital market is efficient in its current state. The LQ45 index on the Indonesia Stock Exchange serves as the study's population. Purposive sampling was used in the sampling technique. The sample consists of thirty companies continuously listed in the LQ45 index between 2017 and 2020. The data used is daily stock price data for companies continuously listed in the LQ45 index for the 2017-2020 period. The information was obtained from www.yahoofinance.com. In this study, data analysis techniques include normality tests, run tests, and correlations. The study's findings indicate that the Indonesian capital market is efficient in its current state.Keywords: market efficiency, efficient capital market, run test, series correlation, weak form market efficiency